Critical phosphorus requirements of Trifolium species: The importance of root morphology and root acclimation in response to phosphorus stress. Issue 3 (30th July 2021) - Becquer, Adeline; Haling, Rebecca E.; Warren, Anne; Alden Hull, Rowan; Stefanski, Adam; Richardson, Alan E.; Ryan, Megan H.; Kidd, Daniel R.; Lambers, Hans; Sandral, Graeme A.; Simpson, Richard J.
Abstract: Differences in root morphology and acclimation to low‐phosphorus (P) soil were examined among eight legume species from the Trifolium Section Tricocephalum to understand how these root attributes determine P acquisition. Ornithopus sativus was included as a highly P‐efficient benchmark species. Plants were grown as microswards in pots with five rates of P supplied in a topsoil layer to mimic uneven P distribution within a field soil profile. Topsoil and subsoil roots were harvested separately to enable measurement of the nutrient‐foraging responses. Critical P requirement (lowest P supply for maximum yield) varied over a threefold range, reflecting differences in root morphology and acclimation of nutrient‐foraging roots to P stress. Among the species, there was a 3.2‐fold range in root length density, a 1.7‐fold range in specific root length, and a 2.1‐fold range in root hair length. O . sativus had the lowest critical P requirement, displayed a high root length density, the highest specific root length, and the longest root hairs. Acquisition of P from P‐deficient soil was facilitated by development of a large root hair cylinder (i.e. a large root–soil interface). This, in turn, was determined by the intrinsic root morphology attributes of each genotype, and the plasticity of its root morphology response to internal P stress. Root acclimation in low‐P soil by all species was mostly associated with preferential allocation of mass to nutrient‐foraging roots. Only O . sativus and four of the Trifolium species adjusted specific root length beneficially, and only O . sativus increased its root hair length in low‐P soil.